2020
DOI: 10.1186/s12302-020-00323-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a test method for transformation of veterinary pharmaceuticals and biocides in anaerobic liquid manure

Abstract: Background: Spreading of manure on agricultural soils represents an important pathway by which veterinary medicinal and biocidal products enter the environment. To assess their environmental impact in the context of authorization processes, experimental testing of transformation of these compounds in manure is considered in regulatory guidance documents. However, there is no standardized experimental test method available so far. To fill this gap, an experimental test method was developed to examine transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…CFT, FLO, TYL and SMX were all observed to be impersistent within pig slurries at a pH of 7 and the DT 50 values were in-line with previous reports of degradation rates within pig slurries/manures and anaerobic digestion (Gilbertson et al, 1990;Hollis, 1991;Mohring et al, 2009;Chatterjee et al, 2013;Berendsen et al, 2018;Junker et al, 2020). Acid or alkaline treatments were observed to increase/decrease degradation rate constants.…”
Section: Antibiotic Degradation As a Function Of Phsupporting
confidence: 90%
See 2 more Smart Citations
“…CFT, FLO, TYL and SMX were all observed to be impersistent within pig slurries at a pH of 7 and the DT 50 values were in-line with previous reports of degradation rates within pig slurries/manures and anaerobic digestion (Gilbertson et al, 1990;Hollis, 1991;Mohring et al, 2009;Chatterjee et al, 2013;Berendsen et al, 2018;Junker et al, 2020). Acid or alkaline treatments were observed to increase/decrease degradation rate constants.…”
Section: Antibiotic Degradation As a Function Of Phsupporting
confidence: 90%
“…Presently there is a lot of uncertainty regarding veterinary medicine degradation within manures due to differences in manure properties; despite the fact that a thorough understanding is critical for harmonisation of manure degradation studies (EMA, 2011;VICH, 2000;VICH, 2003). Variation exists between manure degradation studies, for example Blackwell et al (2005) reported a DT 50 of 79 d for oxytetracycline within pig slurries whereas Wang et al (2015) calculated a range of 9.05-9.65 d. When regulatory soil degradation studies are performed (e.g., OECD 307), the use of four soil types is usually required due to the known influence of soil properties on the degradation rate and route of organic compounds (OECD, 2002;Junker et al, 2020). Soil matrix properties can affect sorption, hydrolysis, microbial mineralization as well as the ionic strength and speciation of contaminants (pKa) via changes in pH (Sassman and Lee, 2005;ter Laak et al, 2006;Chatterjee et al, 2013;Jechalke et al, 2014;Mitchell et al, 2014;Junker et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be true for soils where agriculturally used biocides or disinfectants are spread with manure, potentially combined with antibiotics, antiparasitics, or other VMPs. Occurrence and transformation of biocides in manure and their fate in soils are only marginally investigated [ 77 , 78 ]. Moreover, biocide release into the environment could increase due to the SARS-CoV-2 pandemic [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…In surface waters, wastewater treatment effluents are a constant contributor of anthropogenic bioactive compounds including retinoids [253]. To address transformation of pharmaceutically and cosmetically used retinoids, it is suggested that work being initiated at the OECD to develop a test guideline on anaerobic transformation of veterinary pharmaceuticals, organic compounds and biocides in liquid farmyard manure [302] could include retinoid-like monitoring endpoints. This would contribute to filling the assessment data gap of retinoid-like activity originating from farmyard manure and its fate in the environment.…”
Section: Discussion -Implications For Risk Assessmentmentioning
confidence: 99%